2014
DOI: 10.7603/s40790-014-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Validity of a Single Question with Multiple Classification Options for Depression Screening in Medical Settings

Abstract: Keywords-convergent validity; depression screening; single question; BDI-II; severity level I. INTRODUCTIONDepression is one of the most common mental illnesses globally in both medical and non-medical populations. The World Health Organization noted that in 17 countries 1 in 20 people reported having an episode of depression in the past year [1]. In the United States, the Centers for Disease Control and Prevention reported a 9.1% prevalence rate of current depression in the general population [2]. Reference [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…2C). These results indicated that 20-30% of judgments differed based on race, supporting the results of previous studies 9,10,11,12 . Our experiment revealed that "fear" perceived on target faces by Westerners tended to be perceived as "surprise" by East Asians.…”
Section: Projection Map Of Observer's Vote Ratessupporting
confidence: 90%
See 1 more Smart Citation
“…2C). These results indicated that 20-30% of judgments differed based on race, supporting the results of previous studies 9,10,11,12 . Our experiment revealed that "fear" perceived on target faces by Westerners tended to be perceived as "surprise" by East Asians.…”
Section: Projection Map Of Observer's Vote Ratessupporting
confidence: 90%
“…Previous studies on the racial differences of observers 9,10,11 reported that the precision of FER (percentage of estimated labels that correctly matched the label of the facial images) differed depending on the race of the observer. Additionally, the study of Fouty et al 12 revealed statistically signi cant differences in precision between observers of different races. However, there is still uncertainty regarding which emotions are confused across different races.…”
Section: Effect Of Observer's Cultural Background On Fermentioning
confidence: 95%